USE OF PRONOUNS IN NAVOI'S WORKS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Today, learning the Uzbek language as a whole system, raising its logical culture to the level of modern requirements becomes a component of our life. The advancement of our mother tongue to the level of state policy has set high tasks for our linguistics. Currently, Uzbek linguistics is reaching a significant level of convergence. In this article, the lexical-semantic features of the pronouns in the works of Alisher Navoi are thoroughly analyzed, the speech possibilities inherent in the pronouns and their analysis are put on a scientific basis.